Correlation study of microwave non destructive testing (MNDT) and ultrasonic pulse velocity (UPV) on concrete block: article / Mohd Hafiz Abu Bakar - Abu Bakar, Mohd Hafiz
The main objective of this project is to study the relationship of the electrical properties by using microwave non destructive testing (MNDT) and ultrasonic pulse velocity (UPV). In this project, ten sample of concrete block are use. The electrical properties of interest in microwave non destructive testing (MNDT) are dielectric constant, loss factor and loss tangent, but for ultrasonic pulse velocity (UPV) the properties that involved are path length, velocity and also the transit time that the wave propagate from transmitter to the receiver.